2010
DOI: 10.1038/labinvest.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of ultrastructure and cytoskeleton during progression of cardiac hypertrophy to heart failure

Abstract: Studies at the morphological and molecular level have found that transgenic (Tg) mice that overexpress myotrophin in the heart develop hypertrophy at the early age of 4 weeks; this condition worsens to heart failure (HF) at approximately 36 weeks. However, how the sustained effects of alteration in cytoarchitecture of the contractile machinery lead to malfunction of the normal heart remains unclear. Our data have shown that at 4 weeks, the cytoarchitecture observed in left ventricular (LV) tissue samples of Tg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…Among the differentially expressed genes, some were previously associated with HF, such as ACTA1, VCL, NEB, and MYH6. 21,22 Furthermore, the RNA-Seq results were consistent with data from previous studies. It is well described that the upregulation of collagen genes has been associated with the fibrosis process 27 and the increased expression of membrane-associated proteins, such as VLC, 9 has an adaptive response to cellular integrity loss.…”
Section: Discussionsupporting
confidence: 89%
“…Among the differentially expressed genes, some were previously associated with HF, such as ACTA1, VCL, NEB, and MYH6. 21,22 Furthermore, the RNA-Seq results were consistent with data from previous studies. It is well described that the upregulation of collagen genes has been associated with the fibrosis process 27 and the increased expression of membrane-associated proteins, such as VLC, 9 has an adaptive response to cellular integrity loss.…”
Section: Discussionsupporting
confidence: 89%
“…These changes included electron-lucent areas which corresponded to a loss of cristae in these mitochondria; suggesting defective oxidative phosphorylation to generate ATP. In addition, swollen mitochondria, which are reported to be associated with cellular ATP depletion, were present [29]. Vesicle-like structures, likely to be autophagic bodies were also observed in some mitochondria which suggested eventual mitochondrial loss via autophagy in cachectic muscle [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (10,11) have shown that beta tubulin increases in animal models of heart failure, and it is thought that the accumulation of cytoskeletal proteins like tubulin can reduce contractile function of the heart through interfering with contractile proteins or depleting energy reserves by utilizing ATP for synthesis. Increases in cytoskeletal proteins such as tubulin, however, may be a compensatory mechanism of the cardiomyocyte to adapt to the cellular disruption that occurs in response to increases in diastolic filling pressure and wall stress associated with Cre activation and transient systolic dysfunction in this model (16).…”
Section: Discussionmentioning
confidence: 99%